Investigating the impact of soil type, soil moisture, and soil surface residue cover on the efficacy of Diflufenican - Effertz, Andrew David, author; Westra, Phil, advisor; Dayan, Franck, committee member; Khosla, Raj, committee member (Colorado State University. Libraries, 2021)
Diflufenican is a pre-emergent and early post-emergent herbicide that inhibits phytoene desaturase, an essential enzyme in the biosynthesis of carotenoids. It has been used effectively in overseas markets such as Europe and Australia, but it never has been registered for use in the United States. With the herbicide resistance issues in the United States continuing to increase each year, the necessity for developing effective options to combat herbicide-resistant weeds magnifies. Recently, Bayer CropScience has begun research into developing diflufenican as a tool to manage herbicide-resistant weeds, namely Palmer amaranth (Amaranthus palmeri), in United States' corn and soybean systems. In this thesis, research is presented on the impacts soil type, soil moisture, and soil surface residue cover have on diflufenican efficacy. Broad-spectrum weed control with diflufenican was reduced when applied to soils with higher organic matter. This is a consequence of diflufenican having higher sorption coefficients in soils with higher organic matter. Control of Palmer amaranth with diflufenican was not impacted by soil moisture when applied to sandy soils. Under increasing levels of corn residue cover, control of redroot pigweed (Amaranthus retroflexus) was not impacted in the field or the greenhouse. In the greenhouse, control of Palmer amaranth with diflufenican was reduced when applied at a lower rate to the highest corn residue coverage in comparison to treatments with no residue cover. Indications are that when robust rates of diflufenican are applied to soil surfaces with high corn residue cover, necessary control can be expected of susceptible species.
Keywords: Diflufenican; Palmer amaranth; resistance; herbicide; corn; pre-emergent